The effect of NPK fertilization and the plant density on maize yield and bioethanol production - Boros, Beáta; Sárvári, Mihály (Acta Agraria Debreceniensis, 2010)
For industrial (bioethanol) production of maize, a new production technology is needed. I tested and selected hybrids appropriate for this purpose and set up fertilization and plant density experiments. The experiment were set up on chernozem soil in 2008. In bioethanol production, the selection of a high-yielding hybrid with high starch content, a slight reduction of N, increase of potassium, the application of the highest plant densities of the optimum interval, harvest at full maturity (when starch content is the highest compared to protein content) are of great importance.